Community Participation in Agrotourism Management at Waturaka Village, Kelimutu District, Ende Regency: Partisipasi Masyarakat dalam Pengelolaan Agrowisata di Desa Waturaka, Kecamatan Kelimutu, Kabupaten Ende - Dhiki, Katarina; Longginus Saji (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research aims to measure the level of local community participation and determine the forms of their participation in agrotourism management activities in Waturaka Village, Kelimutu District, Ende Regency. The research uses quantitative methods. Data was collected by distributing questionnaires to 95 respondents who were farming actors in the Waturaka agrotourism area. The sample size is determined based on the Slovin formula. Data analysis used quantitative descriptive techniques with the help of the Statistical Package for the Social Sciences (SPSS) version 25 program. The results of the analysis showed that the level of local community participation was very high in agrotourism management activities in Waturaka village, as evidenced by the average questionnaire score of 4.41. Meanwhile, direct observation results show several forms of local community participation, including agricultural land management, active in irrigation construction programs, supporting walls construction, and road repairs, also presents attractions to tourists, promotes and sells agricultural products, and participates in evaluation meetings related to agrotourism management in their village. The very high level of community participation is a very important aspect, so there is no concern if agrotourism management activities in Waturaka village are still running today since they were promoted in 2012 by the Non Government Organization Swisscontact in collaboration with the Ende Regency Tourism Office. Therefore, it is highly hoped that the community will maintain its participatory spirit, and all stakeholders should continue to strive for good cooperation and coordination so that agrotourism management in Waturaka village can develop optimally.